2019
DOI: 10.1177/0022057419877393
|View full text |Cite
|
Sign up to set email alerts
|

Headteachers’ Management Styles and Teachers’ Role Performance in Secondary Schools in Tororo District, Uganda

Abstract: This mixed-methods study stems from the poor learner performance in secondary schools in Tororo District, Uganda, which connoted low teacher role performance and gaps in headteachers’ management styles. Management styles of 28 headteachers and role performance of 294 teachers were investigated. Headteachers mainly used democratic management style, 21 (75.0%); followed by balanced-oriented style, 6 (21.43%); and laissez-faire style, 1 (3.5%). Teachers’ role performance was moderate ( M = 64.75, SD = 10.80). Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The result means that according to the experimental group, 58.4% of the variance in positive school climate is explained by moral leadership; meanwhile, according to the control group, 76.6% of the variance in positive school climate is explained by moral leadership. The result was coherent with some other published papers, which argued that moral leadership influences positive school climate (Oketcho et al, 2020;Katewa & Heystek, 2019;Wenno, 2017;Abu Nasra & Arar, 2020;York-Barr & Duke, 2004;Farling et al, 1999;Manuel, 2017;Aubrey et al, 2012;Bush & Glover, 2016;Dolph, 2016;Schueler, 2018;Grunes et al, 2013;Chen et al, 2017). Therefore, according to the experimental group, as well as the control group, moral leadership strongly predicts a positive school climate.…”
Section: Descriptive Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…The result means that according to the experimental group, 58.4% of the variance in positive school climate is explained by moral leadership; meanwhile, according to the control group, 76.6% of the variance in positive school climate is explained by moral leadership. The result was coherent with some other published papers, which argued that moral leadership influences positive school climate (Oketcho et al, 2020;Katewa & Heystek, 2019;Wenno, 2017;Abu Nasra & Arar, 2020;York-Barr & Duke, 2004;Farling et al, 1999;Manuel, 2017;Aubrey et al, 2012;Bush & Glover, 2016;Dolph, 2016;Schueler, 2018;Grunes et al, 2013;Chen et al, 2017). Therefore, according to the experimental group, as well as the control group, moral leadership strongly predicts a positive school climate.…”
Section: Descriptive Analysissupporting
confidence: 87%
“…Moral management skills, professionalism, teaching improvement as well as problem-based teaching influence positively student learning (York- Barr & Duke, 2004;Katewa & Heystek, 2019;; meanwhile, Imhangbe et al (2019) revealed that democratic, autocratic, and laissez-faire leadership together contributed about 68.3% variations of positive school climate. The servant leadership style and the positive school climate are impacted by the vision, influence, credibility, trust, individual study work, and lecturer support (Farling et al, 1999;Manuel, 2017;; at the same time, there is a significant relationship between a leadership team approach and positive school climate (Oketcho et al, 2020;Chen et al, 2017). Partially variation in positive school climate was caused by moral leadership style, management, and admi nistration (Aubrey et al, 2012;Bush & Glover, 2016); meanwhile, Wirawan et al (2019), as well as Dos Santos (2020) found out that leaders' emotional intelligence importantly predicted both task-oriented and relationship-oriented leadership.…”
Section: The Relationship Between Moral Leadership and The Positive S...mentioning
confidence: 99%
“…As compared to the study findings with the research of Jesa and V (2017) that teachers' instruction and participation has great significance for the learning of girl students. Similarly, managing students in the classroom is also a factor of better learning for school students (Oketcho et al, 2019). Moreover, students' way of analyzing the classroom environment and acceptance also matters for their learning skills in schools (Dart et al, 2000).…”
Section: Results In Tablementioning
confidence: 99%
“…The authors observe that motivating teachers and enhancing their performance in schools lies within the purview of the Board of Governors (BOGs), who should provide incentives to achieve this objective. According to Oketcho et al (2020), the administration's acknowledgement of teachers' efforts is a source of encouragement for attaining goals. This means increased participation of boards of governors in school matters leads to heightened motivation among teachers to excel, mainly when the board's engagement is constructive.…”
Section: Discussionmentioning
confidence: 99%
“…Because BOGs are crucial to a school's survival and expansion, it is essential to comprehend their role in ensuring that teachers fulfill the established objectives (Wataba & Biodun, 2018). Oketcho et al (2020) assert that to optimize their subordinates' performance, managers or leaders within an organization must implement appropriate management styles. The Ugandan Education Act (2008) outlines the duties of boards of governors in managing schools under their control.…”
Section: Introductionmentioning
confidence: 99%